2016
DOI: 10.24297/jssr.v10i3.4693
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge of Nurses Regarding Hypertension Management Who are Working in National Institute of Cardiovascular Diseases and Hospital in Bangladesh

Abstract: Hypertension is a chronic disease, which progresses silently and leads to many complications affecting major body organs. Hypertensive patient's awareness may be developed on the various aspects regarding disease and self-care management through the health care providers. Nurses knowledge regarding hypertension plays an important role in the ability to the management of hypertension Patients [Kaur et al., 2007]. This descriptive type of cross-sectional study was conducted to assess the Nurses knowledge regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies have shown that nurses were knowledgeable in hypertension during pregnancy. Study revealed that in terms of normal range of blood pressure, 98% were highly knowledgeable and 92% were found highly knowledgeable in the causes of hypertension during pregnancy [9]. However, the primary health nurses got the lowest average mean of 2.70 to the maternal effects of pre-eclampsia.…”
Section: Knowledgeablementioning
confidence: 94%
“…Studies have shown that nurses were knowledgeable in hypertension during pregnancy. Study revealed that in terms of normal range of blood pressure, 98% were highly knowledgeable and 92% were found highly knowledgeable in the causes of hypertension during pregnancy [9]. However, the primary health nurses got the lowest average mean of 2.70 to the maternal effects of pre-eclampsia.…”
Section: Knowledgeablementioning
confidence: 94%